Contrarian investment strategies : the next generation : beat the market by going against the crowd - Dreman, David N. (New York, NY : Simon & Schuster, 1998)
This book is packed with revelations about modern investing that presents different investing methods that not only work in theory but also in practice.
Includes bibliographical references (p. [421]-447) and index.
rua 24/08/15
Loans
Keywords: Speculation; Stocks; Investments